2004
DOI: 10.1002/ange.200460808
|View full text |Cite
|
Sign up to set email alerts
|

An Organometallic Chemosensor for the Sequence‐Selective Detection of Histidine‐ and Methionine‐Containing Peptides in Water at Neutral pH

Abstract: Mit bloßem Auge sichtbar: Ein Indikator‐Verdrängungstest, basierend auf der Kombination eines metallorganischen Rhodium‐Komplexes mit dem Indikator Azophloxin, ermöglicht die selektive Detektion von Histidin‐ oder Methionin‐haltigen Peptiden in Wasser bei neutralem pH‐Wert (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
14
0
3
Order By: Relevance
“…Complexes of metal–organic half‐sandwich complexes 74 with a variety of dyes, for example, azophloxine ( 75 ), are used as indicator displacement assays for the detection of peptides203 and amino acids204 in aqueous buffer solution. The 74 ⋅ 75 assay ( K a ≈3.2×10 7 M −1 in 100 m M aqueous phosphate buffer solution, pH 7.0) allows differentiation of peptides that contain either His or Met residues at positions one or two from the N terminus from other types of peptides.…”
Section: Self‐assembly and Self‐sorting In Watermentioning
confidence: 99%
“…Complexes of metal–organic half‐sandwich complexes 74 with a variety of dyes, for example, azophloxine ( 75 ), are used as indicator displacement assays for the detection of peptides203 and amino acids204 in aqueous buffer solution. The 74 ⋅ 75 assay ( K a ≈3.2×10 7 M −1 in 100 m M aqueous phosphate buffer solution, pH 7.0) allows differentiation of peptides that contain either His or Met residues at positions one or two from the N terminus from other types of peptides.…”
Section: Self‐assembly and Self‐sorting In Watermentioning
confidence: 99%
“…Similar results for the detection of histidine in small polypeptides have very recently attracted interest. [17,32] In an effort to probe the structural nature of the amino acid receptor ternary complexes formed from the displacement process shown in Scheme 3a, the responses of the chemosensing ensembles [Cu(6)Cl][Tf] and [Cu(7)Cl][Tf] towards enantiomeric amino acid samples were explored. Bis chelation of an amino acid to the chiral C 2 symmetric Cu II complex would be expected to create diastereomeric interactions between the amino acid and the terminal pyrrolidines, which could lead to a preference in binding one enantiomer over another.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Chin et al reported Co III complex 3 that binds amino acids with predictable stereoselectivity, [28] while Corradini et al have pursued enantioselective fluorescence sensing of amino acids through modified cyclodextrin-copper(ii) complexes. [29] The presence of a-amino acids has been detected by utilization of indicator-displacement assays [30][31][32] (IDAs). The IDA method, which has been extensively exploited in our laboratories, [33] extends noncovalent molecular-recognition phenomena towards analytical sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Die Metall-Ligand-Wechselwirkungen ergeben auch in polaren konkurrierenden Lösungsmitteln wie Wasser ausreichend hohe Assoziationskonstanten. [202] Komplexe der metall-organischen Halbsandwichkomplexe 74 mit einer Reihe von Farbstoffen, zum Beispiel Azophloxin (75), werden als Indikatorverdrängungsassays zum Nachweis von Peptiden [203] und Aminosäuren [204] [203] Die pH-Abhängigkeit der Bindungsaffinität von Aminosäu-ren zum Komplex 74 wurde genutzt, um einen Chemosensor zur colorimetrischen Bestimmung der 20 natürlichen Aminosäuren in Wasser zu entwickeln. [204] Makrocyclische Komplexe vom Typ 76 (M = Ru, Rh und Ir, L = Benzol-oder Cyclopentadienylliganden, R = substituierte Aminomethylgruppen) können als metallorganische Analoga von [12]Krone-3 angesehen werden.…”
Section: Helicale Selbstorganisierte Aggregateunclassified